2021
DOI: 10.3390/jdb9030024
|View full text |Cite
|
Sign up to set email alerts
|

The Role of BMP Signaling in Osteoclast Regulation

Abstract: The osteogenic effects of Bone Morphogenetic Proteins (BMPs) were delineated in 1965 when Urist et al. showed that BMPs could induce ectopic bone formation. In subsequent decades, the effects of BMPs on bone formation and maintenance were established. BMPs induce proliferation in osteoprogenitor cells and increase mineralization activity in osteoblasts. The role of BMPs in bone homeostasis and repair led to the approval of BMP2 by the Federal Drug Administration (FDA) for anterior lumbar interbody fusion (ALIF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 193 publications
(270 reference statements)
0
19
0
Order By: Relevance
“…Irregular activities of these bone cells can lead to juvenile osteoporosis in childhood, or osteopenia and osteoporosis later in adulthood [ 5 , 54 ]. While it is suggested that these bone disorders may arise due to hyperactivity of osteoclasts, the function of these bone resorption cells isolated directly from humans is not established [ 1 , 18 ]. Therefore, there is an urgent need to establish a reliable method of isolating viable bone marrow cells that can be differentiated into osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Irregular activities of these bone cells can lead to juvenile osteoporosis in childhood, or osteopenia and osteoporosis later in adulthood [ 5 , 54 ]. While it is suggested that these bone disorders may arise due to hyperactivity of osteoclasts, the function of these bone resorption cells isolated directly from humans is not established [ 1 , 18 ]. Therefore, there is an urgent need to establish a reliable method of isolating viable bone marrow cells that can be differentiated into osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoblasts are mononucleated cells responsible for forming new bone and derive from mesenchymal stem cell (MSC) progenitors [ 11 , 12 , 13 , 14 ]. Contrarily, osteoclasts are multinucleated immune cells that derive from hematopoietic stem cells (HSCs) and resorb old or damaged bone [ 8 , 10 , 15 , 16 , 17 , 18 ]. The crosstalk between these two cell types is critical for the formation of early structures, such as digits, and bone homeostasis throughout adulthood [ 1 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BMPs are a group of proteins that belong to the superfamily of transforming growth factor-β (TGF-β) [ 41 ]. These proteins were initially discovered for their osteoinductive properties [ 42 ]. Nowadays, BMPs are extensively studied in animal models of bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that BMP2 and -7 increase osteoblastic differentiation markers ( 34 , 90 ), and that BMP signaling promotes chondrocyte differentiation ( 91 ). By acting on osteoblasts and chondrocytes, BMPs enable process of endochondral bone formation and ossification ( 92 ). In osteoblasts, BMPs act in a complex interaction with several signaling pathways, including Wnt, Notch, Hedgehog and FGF ( 89 , 93 ).…”
Section: Bmp Function In Osteoclastsmentioning
confidence: 99%